Steps towards a realisation of the right to have a nationality - Groot, Gerard-René de (Lexonomica, 2024)
International standards regarding the acquisition and loss of nationality are increasingly being developed by various international institutions. This paper focusses on standard setting (in particular by the United Nations, the Council of Europe and the European Union) with relevance for European countries. While international treaties on or including rules on nationality law are addressed, attention is also given to soft law instruments such as guidelines and recommendations. Moreover, several new standards have also emerged from the decisions of international courts. The authors conclude that all these rules have as result that the margin of appreciation for national governments and courts in matters related to nationality law matters is getting increasingly smaller.
Keywords: acquisition of nationality; citizenship; loss of nationality; nationality; naturalization; quasi-loss of nationality